Utilization of Customs Regulations Related to Import Export Insurance in Supporting the Export Process - Ardiansyah (Jurnal Abdimas Peradaban, 2022)
The impact of the ongoing COVID-19 pandemic requires a precise strategy to encourage export activities. This community service activity aims to provide education for practitioners and academics in the insurance sector in understanding more deeply the use of customs regulations related to import export insurance in order to strengthen the important role of trade insurance and marine cargo in supporting the export process. There are various customs regulations that can be used by businesses related to insurance, namely: First, the use of domestic insurance will reduce the payment of import duties and taxes for imports because they are not included in the import value. Second, the use of guarantees from insurance companies (customs bonds) as a solution for paying state levies for companies that are unable to pay off these levies immediately and in utilizing customs facilities aimed at boosting national export performance. Among the customs facilities that can be utilized are bonded zone and Import Facility for Export Purpose (KITE). Both facilities are intended to provide fiscal and procedural facilities to producer exporters. The use of customs facilities requires guarantees for import duties and import taxes. One type of guarantee is a guarantee from an insurance company (customs bond). Based on this activity, participants can take advantage of customs regulations related to import-export insurance which ultimately aims to encourage export activities, especially during this pandemic.